2021
DOI: 10.1158/1078-0432.ccr-21-0325
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Source, Automated Tumor-Infiltrating Lymphocyte Algorithm for Prognosis in Triple-Negative Breast Cancer

Abstract: Purpose: Although tumor-infiltrating lymphocytes (TIL) assessment has been acknowledged to have both prognostic and predictive importance in triple-negative breast cancer (TNBC), it is subject to inter and intraobserver variability that has prevented widespread adoption. Here we constructed a machine-learning based breast cancer TIL scoring approach and validated its prognostic potential in multiple TNBC cohorts. Experimental Design: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…The machine-defined TILs variables were constructed using five different methods, as previously described. 17 The first and established method was to calculate eTIL% representing the proportion of TILs over tumor cells, calculated as (TILs/TILs + tumor cells) x 100. 1 Four additional methods were used to measure TILs as follows: Measurement of the proportion of TILs over total cells: etTIL % = (TILs/total cells) x 100 Measurement of the proportion of TILs over stromal cells: esTIL % = (TILs/total cells – tumor cells) × 100 Measurement of the density of TILs over tumor region: eaTILs (mm 2 ) = TILs/sum of tumor region areas analysed (mm 2 ) Measurement of the density of TILs over stromal area: easTIL % = [sum of TIL area (mm 2 ) /stroma area (sum of tumor region areas analysed (mm 2 ) – sum of tumor cell area (mm 2 ))] × 100 …”
Section: Methodsmentioning
confidence: 99%
“…The machine-defined TILs variables were constructed using five different methods, as previously described. 17 The first and established method was to calculate eTIL% representing the proportion of TILs over tumor cells, calculated as (TILs/TILs + tumor cells) x 100. 1 Four additional methods were used to measure TILs as follows: Measurement of the proportion of TILs over total cells: etTIL % = (TILs/total cells) x 100 Measurement of the proportion of TILs over stromal cells: esTIL % = (TILs/total cells – tumor cells) × 100 Measurement of the density of TILs over tumor region: eaTILs (mm 2 ) = TILs/sum of tumor region areas analysed (mm 2 ) Measurement of the density of TILs over stromal area: easTIL % = [sum of TIL area (mm 2 ) /stroma area (sum of tumor region areas analysed (mm 2 ) – sum of tumor cell area (mm 2 ))] × 100 …”
Section: Methodsmentioning
confidence: 99%
“…TIL detection has been framed as a nuclear classification and segmentation problem. Earlier nuclear segmentations had been performed using thresholding, 47 watershed algorithms, 48 and many variations of active contours. 49,50 Although performance is limited by variations in staining, overlapping nuclei, and small and complex shapes of nuclei, these algorithms remain popular in research.…”
Section: T U M O U R -I N F I L T R a T I N G L Y M P H O C Y T E S (...mentioning
confidence: 99%
“…Recently, recommendations have been published from the international immuno-oncology group to aid towards clinical validation [103]. In BC, the clinical significance of digital TILs enumeration has been explored [65,[104][105][106][107]. In a recent study by Bai et al, a semisupervised neural network was developed for the scoring of digital TILs in 920 early TNBC patients and demonstrated that increasing digital TILs density was a favorable prognostic factor [104].…”
Section: Ai-assisted Evaluation Of Time On Hande Breast Cancer Tissue...mentioning
confidence: 99%
“…In BC, the clinical significance of digital TILs enumeration has been explored [65,[104][105][106][107]. In a recent study by Bai et al, a semisupervised neural network was developed for the scoring of digital TILs in 920 early TNBC patients and demonstrated that increasing digital TILs density was a favorable prognostic factor [104]. Furthermore, retrospective analyses of prospective cohorts that recruited a large sample of BC patients, concluded that digital TILs counts independently predicted pCR [105,106].…”
Section: Ai-assisted Evaluation Of Time On Hande Breast Cancer Tissue...mentioning
confidence: 99%
See 1 more Smart Citation